Determinant of Malaysia's household debt by using macroeconomics variables / Jasmin Archad and Norsyafawani Md Nor - Archad, Jasmin; Md Nor, Norsyafawani (Faculty of Business and Management, 2016)
This study is conducted to determine the relationship between macroeconomics variables which are Gross Domestic Product (GDP), Interest Rate (IR), Consumer Price Index (CPI), House Price Index (HPI), Income (INC) and Consumption (CONS) towards the Household Debt (HHD) in Malaysia. The variable used to measure the Household Debt is the total of secured and unsecured debt by the household. The quarterly data of dependent and independent variables was collected started from Q1 2006 until Q4 2015 from Thomson One DataStream, EIU Country Data and BNM Statistical Data. The results further our understanding regarding on the relationship between macroeconomics variables towards the Household Debt in Malaysia. In Single Linear Regression Model (SLR) and Multiple Linear Regression (MLR), the study found that Gross Domestic Product (GDP) and Consumption (CONS) have significant negative relationship towards Household Debt (HHD). On the other hand, Interest Rate (IR), Consumer Price Index (CPI), House Price Index (HPI) and Income (INC) shows insignificant relationship with Household Debt (HHD).